Genetic studies on a new deficiency gene (PI*Ztun) at the PI locus. Issue 12 (December 1989) - Whitehouse, D B; Abbott, C M; Lovegrove, J U; McIntosh, I; McMahon, C J; Mieli-Vergani, G; Mowat, A P; Hopkinson, D A
Abstract : During a study of the alpha 1 antitrypsin (AAT) protein and its locus (PI) by high resolution isoelectric focusing and direct molecular analysis of 106 PIZ probands and their families, a new allele (Ztun) was identified that resembles Z in many of its properties. Two sibs, both compound heterozygotes for Ztun and Z, showed similar evidence of mild liver involvement that was indistinguishable from that associated with classical ZZ homozygotes. The Ztun protein appeared to be deficient in the plasma to about the same degree as the Z protein. Allele specific oligonucleotide analysis of amplified genomic DNA indicated that the new allele is the result of a mutation in exon V that is identical to the classical G—-A transition at codon 342 that results in the Glu—-Lys substitution characteristic of the Z allele. An analysis of DNA haplotypes constructed from polymorphic restriction enzyme recognition sites in and around the PI locus confirmed that Ztun probably represents a new mutation at codon 342 that has occurred on an M2-like genetic background.